Probabilistic Assessments of Offshore Pipelines Exposed to Corrosion and Free Span - Rayner, Scholastica (IRC, 2019)
There are many causes that can cause the pipelines to fail. Mostly, the pipeline experience failure due to corrosion hazards and freespan hazards. Subsequent to this, probabilistic approach helps to determine the POF of the pipeline using Monte Carlo Stimulation with ease of MATLAB software. Then the Limit State Function (LSF) used in this project was obtained from published literature for both corrosion and freespan. Lastly, the combined POF due to corrosion and freespan failures was obtained and compared.